Decidual and peripheral blood CD4+CD25+ regulatory T cells in early pregnancy subjects and spontaneous abortion cases - Sasaki, Y.; Sakai, M.; Miyazaki, S.; Higuma, S.; Shiozaki, A.; Saito, S. (Molecular human reproduction, 2004)
Human pregnancy represents a situation of semiallograft to maternal host. Therefore, it has been reported that tolerance to the fetal allograft represents a mechanism for maintaining a pregnancy. CD4+CD25bright regulatory T cells are known to play an important role in the development and maintenance of tolerance in peripheral tissues. However, the potential role of CD4+CD25bright T cells in maintaining human pregnancy has not been reported. In this study, we show that early human pregnancy decidua contains an abundance of CD4+CD25bright T cells, which express CD152(CTLA‐4) at a high level. CD4+CD25bright T cells mediate potent inhibition of autologous T‐cell proliferation by anti‐CD3 stimulation. Furthermore, these cells inhibit the proliferation of autologous CD4+CD25– T cells in a dose‐dependent fashion. This suppressive function of decidual CD4+CD25+ T cells required cell‐to‐cell contact. The proportion of decidual CD4+CD25bright T cells was significantly lower in specimens from spontaneous abortion compared to those from specimens from induced abortions. These results suggest that decidual CD4+CD25bright T cells contribute to the mechanisms mediating maternal immune tolerance of conceptus antigens and therefore might contribute to the maintenance of pregnancy.